Impact of generated traffic in construction of Islamic PG, kindergarten, primary school and al Azhar Islamic college in Cairo Palembang - Setiawati, Mira; Royan , Noto; ., Jonizar (International Journal of Engineering and Technology, 2024)
Traffic impact analysis (andalalin) is a special study aimed at assessing the effects caused by traffic generated by the development of the surrounding area. Andalalin is essentially an analysis of the influence of land use development on the surrounding traffic system, caused by the generation of new traffic, traffic displacement and vehicles entering and leaving the study area . As part of this research, the aim is to know the extent of the construction of the Islamic college, kindergarten and elementary school of Al-Azhar, Cairo Palembang and the extension of permits operating premises located on Jl. Jendral Sudirman/road Mohammad Ali Km 3.5, Kemuning District, Palembang City, regarding surrounding traffic and management of resulting traffic impacts. The purpose of the research is to analyze the traffic performance of the Islamic PG Development, Kindergarten, Elementary Schools and Middle Schools of Al-Azhar Cairo Palembang and the expansion of operating permits located on road .Jendral Sudirman/road. Mohammad Ali Km 3.5, Kemuning district, Palembang city. The systematic study process carried out at the initial stage of this traffic impact study involves carrying out traffic modeling and forecasting. The Traffic Impact Monitoring and Assessment Plan addresses significant impacts including vulnerability, road accidents, traffic jams and the level of community unrest around the construction of Al-Azhar Islamic College, kindergarten, primary school, Cairo Palembang and the extension of operating permits. located on road Jendral Sudirman/road. Mohammad Ali Km 3.5 Kemuning District, Palembang City.